05.05 Systematic profiling of mouse synovial fibroblasts during tnf-driven arthritogenesis and alignments to human rheumatoid arthritis. (1st March 2017) - Ntougkos, Evangelos; Chouvardas, Panagiotis; Roumelioti, Fani; Ospelt, Caroline; Frank-Bertoncelj, Mojka; Filer, Andrew; Buckley, Christopher D; Gay, Steffen; Nikolaou, Christoforos; Kollias, George
Abstract : Background: Aberrant activation of synovial fibroblasts (SFs) is a key determinant in the pathogenesis of rheumatoid arthritis (RA). We aimed to produce a systematic map of gene expression and epigenetic changes occurring in this cell type during disease progression in the human TNF-transgenic model of arthritis, as well as identify commonalities with the human disease. Materials and methods: We used deep sequencing to probe the transcriptome, the methylome and the chromatin landscape of cultured mouse arthritogenic synovial fibroblasts at three stages of disease, as well as SFs stimulated with human TNF. We performed bioinformatics analyses at the gene, pathway and network levels, compared mouse and human data and validated selected genes in both species. Results: SF arthritogenicity is reflected on distinct patterns of transcriptional deregulation and is enriched in pathways of the innate immune response and mesenchymal differentiation. A functionally-definable subset of these changes is associated with promoter methylation. The disease state involves highly active promoters, as marked by H3K4 trimethylation. We identified substantial overlap between mouse and human data, at the level of the gene and to an even higher degree at the level of pathways. Conclusions: This work presents the first systematic examination of the pathogenic changes that occur in the mouse synovial fibroblast as TNF-driven arthritogenesis progresses. Comparisons with respective human RA data show significant correlations, further validating the human TNF-transgenic mouse as a reliable model of the human disease. The data generated may serve as a framework for the discovery of novel pathogenic mechanisms and biomarkers that will aid in translational efforts.